Controlling malaria in pregnancy: investigating the factors that influence the uptake of intermittent preventive treatment services in the Nzema-east district, Ghana - Acquah, Augustine Adolf Kwame (2011)
Thesis submitted to the Department of Community Health, School of Medical Sciences, College of Health Sciences, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the award of Master Science Degree in Health Education and Promotion.